Meningkatkan Volume Penjualan Produk UMKM Kelurahan Rungkut Kidul Melalui Pasar Tradisional Berupa Bazar Hari Pahlawan - Arkha Kunta Wijaya Trus Hayu; Muhadjir Anwar (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This research was conducted with the aim of analyzing the effect of bazaars on the sales volume of MSME products in Rungkut Kidul Village. The field observation method was used to collect data from a sample consisting of MSMEs in RW 01 - RW 06 Kelurahan Rungkut Kidul on weekdays and during bazaars. The observed variables include product sales volume per day, marketing strategies used, and consumer behavior in two different market conditions. The analysis technique used is descriptive analysis technique to describe the profile of MSMEs and the sales volume per day. The results of the analysis are expected to illustrate differences in the sales volume of MSME products in different market conditions. The findings of this study are expected to provide guidance for MSME owners and become one of the solutions to the constraints of the quiet market experienced by the majority of MSMEs in Rungkut Kidul Village.